Flor Yeast Diversity and Dynamics in Biologically Aged Wines - David-Vaizant, Vanessa; Alexandre, Hervé (Frontiers in Microbiology, 2018)
Wine biological aging is characterized by the development of yeast strains that develop a biofilm on the wine surface after alcoholic fermentation. These yeasts, known as flor yeasts, form a velum that protects the wine from oxidation during aging. 39 velums aged from one to six years were sampled from “Vin jaune” from two different cellars. We show for the first time that these velums possess various aspects in term of colour and surface aspects. Surprisingly, the heterogeneous velums are mostly composed of one species, Saccharomyces cerevisiae. Scanning electron microscope observations of these velums revealed unprecedented biofilm structures and various yeast morphologies formed by the sole Saccharomyces cerevisiae species. Our results highlight that different strains of Saccharomyces are present in these velums. Unexpectedly, in the same velum, flor yeast succession occurred during the 6 years aging, supporting the assumption that environmental changes are responsible for these shifts. Despite numerous sample wine analyses, very few flor yeasts could be isolated from wine following alcoholic fermentation, suggesting that flor yeast development results from the colonization of yeast present in the aging cellar. We analysed the FLO11 and ICR1 sequence of different Saccharomyces cerevisiae strains in order to understand how the same strain of Saccharomyces cerevisiae could form various types of biofilm. Among the strains analysed, some were heterozygote at the FLO11 locus, while others presented two different alleles of ICR1 (wild type and a 111 bp deletion). We could not find a strong link between strain genotypes and velum characteristics. The same strain in different wines could form a velum having very different characteristics, highlighting a matrix effect.